Análise e caracterização dos públicos de interesse e potencial do streamer Casimiro Miguel - Santos, Bruna Suelem Inacio dos (Brasil, 2024)
This study aims to characterize the audiences of streamer and influencer Casimiro Miguel, in order to highlight and strengthen his brand. The main focus is on the interactivity and involvement of users both on and off the platform, as well as their influence and impact on the virtual community. To underpin the concept of online culture and cyberspace, renowned authors were used as a theoretical basis, including Sherry Turkle, Howard Rheingold, Pierry Lévy and Michael Solomon. The theoretical approach incorporates elements such as writing, data collection, verification and ethics, resulting in scenarios that go beyond the streaming platform and reach a wide audience. In addition, the study explores the impact of interactivity on Twitch and how this shapes audiovisual storytelling within this platform. By analyzing the audiences that consume Casimiro Miguel's content, this work seeks to provide valuable insights into the role of Public Relations on a streaming platform like Twitch and how these strategies can be applied by other content creators seeking prominence and success in the online gaming community.